Differentiation of Petrophysical Reservoir Types of the Lower Famennian Deposit of the Timan-Pechora Province by Hydraulic Flow Units - S. N. Krivoshchekov; D. O. Shirinkin (Vestnik Permskogo Universiteta: Seriâ Geologiâ, 2022)
In oil and gas geology, the problem of uncertainty of the distribution of geological characteristics in the inter-well space of the deposit is relevant. In this paper, we propose a technique to clarify the permeability spatial distribution in the deposits of the Vostochno-Lambeyshorskoye field by classifying core material and allocation petrophysical dependences of permeability on porosity for each class separately. The identification of petrophysical types for complex carbonate reservoirs makes it possible to differentiate the void space and more accurately describe the filtration model, where the presence of cracks in the rock body plays an important role in the fluid moving to the bottom of the well. In the course of the work, the core material was classified according to the flow zone indicator parameter in several ways, the best of which was determined using a pairwise comparison of the Student's t-criteria and determination coefficients.